Human Milk Oligosaccharides Increase Mucin Expression in Experimental Necrotizing Enterocolitis. Issue 3 (10th December 2018) - Wu, Richard You; Li, Bo; Koike, Yuhki; Määttänen, Pekka; Miyake, Hiromu; Cadete, Marissa; Johnson‐Henry, Kathene C.; Botts, Steven R.; Lee, Carol; Abrahamsson, Thomas R.; Landberg, Eva; Pierro, Agostino; et al.
Abstract : Scope: Necrotizing enterocolitis (NEC) is a leading cause of morbidity and death in preterm infants, occurring more often in formula‐fed than breastfed infants. Studies in both rats and humans show that human milk oligosaccharides (HMOs) lower the incidence of NEC, but the mechanism underlying such protection is currently unclear. Methods and Results: By extracting HMOs from pooled human breastmilk, the impact of HMOs on the intestinal mucin levels in a murine model of NEC are investigated. To confirm the results, the findings are validated by exposing human intestinal epithelial cells and intestinal organoids to HMOs and evaluated for mucin expression. HMO‐gavage to pups increases Muc2 levels and decreases intestinal permeability to macromolecular dextran. HMO‐treated cells have increased Muc2 expression, decreased bacterial attachment and dextran permeability during challenge by enteric pathogens. To identify the mediators involved in HMO induction of mucins, it is demonstrated that HMOs directly induce the expression of chaperone proteins including protein disulfide isomerase (PDI). Suppression of PDI activity removes the protective effects of HMOs on barrier function in vitro as well as NEC protection in vivo. Conclusions: Taken together, the results provide insights to the possible mechanisms by which HMOs protect the neonatal intestine through upregulation of mucins. Abstract : Murine pups are gavage‐fed with pooled human milk oligosaccharides and following induction of necrotizing enterocolitis (NEC) are assessed for intestinal injury and mucin expression. The findings are validated in vitro using human intestinal organoids and two tissue culture epithelial cell lines. It has been shown that human milk oligosaccharide feeding reduces intestinal injury, increases goblet cells, and promotes mucin expression.